Assessment of exercise training program effects on ischemia modified albumin serum levels by 4 different laboratory methods. (14th October 2021) - Bradichanski, L; Goldhammer, E; Zaid, G; Tanchilevitch, A; Spevak, I; Maor, I; Mery-Dobrecky, I
Abstract: Background: Ischemia modified albumin (IMA) is an FDA approved marker of ischemia that is produced when serum albumin contacts ischemic tissues. Albumin modification reduces its binding affinity to heavy metal ions such as Cobalt and can be measured by the albumin cobalt binding (ACB) assay and with an enzyme-linked immunosorbent assay (Elisa) for N-terminal-modified Albumin as well. A transient increase in albumin levels at peak exercise due to hemoconcentration is frequently found with resultant decrease in the non-bound portion of cobalt, therefore the ratio IMA/Albumin is often tested as well after exercise. Aim: To evaluate the effect of 12 weeks exercise training program on IMA levels in patients with proven coronary artery disease (CAD), by four different laboratory methods. Methods: 40 patients were enrolled to study, with either a recent (<1 month) myocardial infarction (MI), percutaneous coronary intervention (PCI), or an aorto-coronary by-pass surgery (CABG). All underwent a 12 weeks aerobic exercise program, 50 minutes sessions, 3–4/week, at 75–80% of their maximal exercise test (EXT) heart rate. IMA assessment was done with the ELISA and the ACB assay, IMA-Elisa/Serum Albumin, and ACB-IMA/Serum Albumin ratios, pre and post EXT, at baseline (BL-EXT1 & 2), and at end program (EP-EXT1&2). The Generalized Linear Mixed Model (GLMM) was used to determine the intervention time effect, for the time variant exercise measures and for time invariant measures (age, gender, risk factors, EF%). Results: In three out of the four methods a time effect (program effect) was found, EP-EXT2 IMA levels were lower than BL-EXT2 (ACB = p<0.01; ACB/ALB = p<0.01; IMA/ALB = p<0.05), meaning a beneficial effect of exercise program. In post CABG patients, the IMA-ELISA levels were higher only at BL, p<0.05. When PCI was applied, only ACB/ALB ratio was lower, p<0.001. Exercise duration and METS had similar effect, reducing only ACB/ALB ratio, p<0.01 & p<0.05 respectively. The only time invariant measurement that proved to have an effect on IMA was the %EF, as detected only by the IMA-Elisa method and by the IMA-Elisa/Albumin ratio along the intervention program time, p<0.05 & p<0.05, respectively. EF% was negatively associated with these outcome differences, the lower the EF%, the higher was the IMA level. When EXT was diagnosed positive for of ischemia, then a positive association with the ΔIMA-ACB levels (p<0.05) was found. Conclusions: Exercise training program effects on IMA levels in chronic IHD patients could be detected by the accepted IMA laboratory tests however when time variant and time invariant measures were analyzed with the use of one or two methods only several program effects could have been missed. The inclusion of the two IMA/Albumin ratios using the same blood samples offered additional important information. Funding Acknowledgement: Type of funding sources: None.